Framing Machine Learning Opportunities for Hypotension Prediction in Perioperative Care: A Socio-technical Perspective - Ghosh, Pratik; Posner, Karen L.; Hyland, Stephanie L.; Hyland, Stephanie; Cleve, Wil van; Bristow, Melissa; Long, Dustin R.; Palla, Konstantina; Nair, B.; Fong, Christine; Pauldine, Ronald; Vavilala, M.; et al. (ACM Transactions on Computer-Human Interaction, 2023)
Hypotension during perioperative care, if undetected or uncontrolled, can lead to serious clinical complications. Predictive machine learning models, based on routinely collected EHR data, offer potential for early warning of hypotension to enable proactive clinical intervention. However, while research has demonstrated the feasibility of such machine learning models, little effort is made to ground their formulation and development in socio-technical context of perioperative care work. To address this, we present a study of collaborative work practices of clinical teams during and after surgery with specific emphasis on the organisation of hypotension management. The findings highlight where predictive insights could be usefully deployed to reconfigure care and facilitate more proactive management of hypotension. We further explore how the socio-technical insights help define key parameters of machine learning prediction tasks to align with the demands of collaborative clinical practice. We discuss more general implications for the design of predictive machine learning in hospital care.